An internal electrode copper paste for low-temperature co-fired ceramic and a preparation method and application thereof

CN121281928BActive Publication Date: 2026-10-09GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511394837.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-12-30
Filing Date
2025-09-26
Publication Date
2026-10-09
Estimated Expiration
2045-09-26

AI Technical Summary

Technical Problem

[0003]为解决现有内电极铜浆与多层陶瓷基板之间不能很好结合的技术问题,本发明的目的在于提供一种用于低温共烧陶瓷的内电极铜浆的制备方法

Benefits of technology

[0020] 1. This invention uses ascorbic acid as a reducing agent, polyethylene glycol as a stabilizer, and PVP as a dispersant. These three are mixed to form a coating solution. Copper powder is pretreated using a coating method. Then, the pretreated copper powder is matched with an organic carrier scheme to produce a high-quality copper paste with good rheological properties, resistance to agglomeration and sedimentation, and excellent stability. The copper paste coating method and the glass powder allow the paste to be sintered at high temperatures for extended periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121281928B_ABST
    Figure CN121281928B_ABST
Patent Text Reader

Abstract

The application belongs to the field of fine chemical industry and low-temperature co-fired ceramic technology, and discloses a kind of inner electrode copper paste for low-temperature co-fired ceramic and its preparation method and application.The method is to add ascorbic acid, polyethylene glycol and polyvinylpyrrolidone into ethanol, and then oil bath stirring to obtain an organic coating solution, and then add copper powder to obtain copper powder coated with polyvinylpyrrolidone film;Silicon dioxide, boric acid, calcium carbonate, sodium carbonate, potassium carbonate and copper oxide are mixed to obtain a mixed powder, which is sintered at 1200-1500℃ to form a glass liquid, and then water-quenched to obtain borosilicate glass powder;Mix solvent, binder, thixotropic agent and additive A to obtain an organic carrier;Magnetic stirring of copper powder coated with polyvinylpyrrolidone film, glass powder, organic carrier and additive B, three-roll grinding and leveling are used to obtain inner electrode conductive copper paste.The method produces conductive copper paste with high-temperature long-time holding performance, good printing performance and excellent conductive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of fine chemicals and low-temperature co-fired ceramics (LTCC) technology, and more specifically, relates to an internal electrode copper paste for low-temperature co-fired ceramics, its preparation method and application. Background Technology

[0002] In recent years, with the rapid development of science and technology, electronic products have gradually shifted towards high integration, lightweighting, and miniaturization. Electronic pastes, as fundamental raw materials for electronic products, are widely used in thick-film circuits, resistors, multilayer ceramic capacitors, touchscreens, battery electrodes, and other technical fields. Among these, electrode pastes for Low Temperature Co-fired Ceramic (LTCC) technology are a key technology that the country needs to focus on solving. Currently, commonly used pastes are precious metal pastes, mainly composed of gold, silver, and palladium, which are costly. Therefore, there is a need to develop new base metal electronic pastes with cost advantages. Because copper is relatively inexpensive, widely available, and possesses excellent electrical and thermal conductivity, copper electrode pastes have the potential to replace traditional precious metal pastes. However, during the processing of copper paste, copper powder is prone to oxidation and agglomeration; the paste has a short storage time and generally requires on-site mixing. The co-firing compatibility between copper paste and substrate materials is poor, specifically manifested in insufficient bonding after sintering (poor adhesion), incompatible sintering conditions, and inability to maintain high temperatures for extended periods. Commercially available high-temperature copper pastes are limited to around 700℃, primarily used as terminal electrodes in multilayer ceramic capacitors, and are difficult to apply to LTCCs (800-950℃). Therefore, there is an urgent need to develop dedicated electronic pastes capable of long-term (>6 hours) high-temperature (>930℃) operation. Summary of the Invention

[0003] To address the technical problem of poor bonding between existing internal electrode copper paste and multilayer ceramic substrates, this invention aims to provide a method for preparing internal electrode copper paste for low-temperature co-fired ceramics. This method utilizes organic coating to obtain copper powder with good oxidation resistance and strong dispersibility. By designing the components of the organic carrier, a paste with good printability, low sedimentation rate, and stable storage can be obtained. Using specifically designed glass powder, the internal electrode copper paste prepared with this glass powder exhibits good co-firing compatibility with the multilayer ceramic substrate, possesses the ability to withstand high temperatures for extended periods, and demonstrates good printability and excellent electrical conductivity.

[0004] The objective of this invention is achieved through the following technical solution:

[0005] A method for preparing internal electrode copper paste for low-temperature co-fired ceramics includes the following steps:

[0006] S1. The reducing agent ascorbic acid, the stabilizer polyethylene glycol and the dispersant polyvinylpyrrolidone are added to an ethanol aqueous solution and stirred in an oil bath at 50-80°C to obtain an organic coating solution. Copper powder is then added and stirred in an oil bath. The mixture is then homogenized, allowed to stand, the supernatant is discarded, and the mixture is dried in a protective atmosphere or a reducing atmosphere to obtain copper powder coated with a polyvinylpyrrolidone film.

[0007] S2. After mixing silicon dioxide, boric acid, calcium carbonate, sodium carbonate, potassium carbonate and copper oxide, add solvent and ball mill. After sieving and drying, a mixed powder is obtained. The mixed powder is heated to 400-500℃ and held at that temperature. Then, it is heated to 1200-1500℃ and sintered to make a glass melt. The glass melt is poured into cold water for water quenching. After the glass cools down, it is ball milled, sieved and dried to obtain borosilicate glass powder.

[0008] S3. Mix the solvent, binder, thixotropic agent, dispersant, defoamer, silane coupling agent and additive A, and magnetically stir in an oil bath at 60-85°C to obtain an organic carrier;

[0009] S4. Copper powder coated with polyvinylpyrrolidone film, borosilicate glass powder, organic carrier and additive B are magnetically stirred, and then ground and leveled using a three-roll mill. After each rolling, the gap is adjusted to 0.2-0.5 mm, and the rolling is repeated to obtain conductive copper paste with internal electrodes.

[0010] Preferably, the copper powder in step S1 has a purity of 99% or higher and an average particle size of 500-2000 nm; the volume ratio of the copper powder to the organic coating liquid is 1:(8-20); the concentration of the ethanol aqueous solution is 40-80 wt%; and the mass ratio of ascorbic acid, polyethylene glycol, and polyvinylpyrrolidone is (2-5):(2-4):1.

[0011] Preferably, in step S2, the mass ratio of silicon dioxide, boric acid, calcium carbonate, sodium carbonate, potassium carbonate, and copper oxide is (12-30):(26-55):(22-50):(0.5-10):(0.5-10):(0.1-5); and the mass ratio of the solvent to the total mass of silicon dioxide, boric acid, calcium carbonate, sodium carbonate, potassium carbonate, and copper oxide is 1:(0.5-2).

[0012] Preferably, the solvent in step S2 is anhydrous ethanol and / or deionized water; the sieve used for sieving is 200-400 mesh; the protective atmosphere is nitrogen, argon, helium, or neon; the reducing atmosphere is a nitrogen-hydrogen mixture, wherein the hydrogen content is 0.5-3 vol‰ of the nitrogen-hydrogen mixture; the drying temperature is 80-160°C; the heating rate to 400-500°C is 2-8°C / min; and the heating rate to 1200-1500°C is 5-20°C / min.

[0013] Preferably, the mass ratio of solvent, binder, thixotropic agent, dispersant, defoamer, silane coupling agent and additive A in step S3 is (15-85):(0.5-10):(0.1-10):(0.1-10):(0.1-10).

[0014] More preferably, the solvent is one or more selected from terpineol, butyl carbitol, butyl carbitol acetate, dodecayl alcohol ester, or triethanolamine; the binder is one or more selected from ethyl cellulose, dioctyl phthalate, polyvinyl alcohol, and palmitic acid; the thixotropic agent is one or more selected from hydrogenated castor oil, acrylic resin, glyceryl trioleate, polyamide wax, and ethyl acetate; the dispersant is one or more selected from castor oil, OP emulsifier, tributyl phosphate, and Span 85; the defoamer is defoamer GPE-3000 or defoamer GP330; the silane coupling agent is KH-550 aminosilane coupling agent; and the additive A is one or more selected from ethyl acetate, ethyl silicone oil, acetone, and methyl ethyl ketone.

[0015] Preferably, the mass ratio of copper powder, borosilicate glass powder, organic carrier and additive B in the polyvinylpyrrolidone film coating in step S4 is (60-80):(0.5-15):(15-40):(0.1-2).

[0016] More preferably, the additive B is one or more of lead zirconate titanate ceramic particles, alumina, copper oxide, bismuth oxide, and boron powder, and the particle size of the additive B is 1 to 20 μm.

[0017] Preferably, the stirring time in step S1 is 0.5–6 h, the homogenization time is 0.5–3 h, and the drying temperature is 60–90 °C; the sintering time in step S1 is 30–120 min, and the cold water temperature is 15–28 °C; the stirring time in step S4 is 0.5–3 h, the rolling is performed 5–10 times, and the parameters of the three-roll mill are: the gap between the low-speed roll and the medium-speed roll is 0.5–3 mm, and the gap between the medium-speed roll and the high-speed roll is 0.5–2 mm.

[0018] An internal electrode copper paste for low-temperature co-fired ceramics is prepared by the method described above.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. This invention uses ascorbic acid as a reducing agent, polyethylene glycol as a stabilizer, and PVP as a dispersant. These three are mixed to form a coating solution. Copper powder is pretreated using a coating method. Then, the pretreated copper powder is matched with an organic carrier scheme to produce a high-quality copper paste with good rheological properties, resistance to agglomeration and sedimentation, and excellent stability. The copper paste coating method and the glass powder allow the paste to be sintered at high temperatures for extended periods.

[0021] 2. This invention utilizes organic materials to coat copper powder, which effectively improves the oxidation resistance of copper paste and requires fewer types of raw materials. The copper powder is spherical copper powder obtained by electrolysis, stored in an oxygen-free environment, and exhibits no oxidation during use. The copper powder particle size is 0.2–3 μm. Furthermore, the glass powder allows the copper paste to be sintered at high temperatures for extended periods, which is more conducive to co-firing with low-temperature co-fired ceramic (LTCC) substrates and results in good adhesion. Attached Figure Description

[0022] Figure 1 Comparison of scanning electron microscope images of copper powder before and after treatment in Examples 1-4.

[0023] Figure 2 The XRD patterns of the copper powder after coating in Examples 1-4 are shown.

[0024] Figure 3 This is a scanning electron microscope (SEM) image of the conductive copper film obtained after sintering the copper paste in Example 1.

[0025] Figure 4 This is a scanning electron microscope (SEM) image of the conductive copper film obtained after sintering the copper paste in Example 2.

[0026] Figure 5 This is a scanning electron microscope (SEM) image of the conductive copper film obtained after sintering the copper paste in Example 3.

[0027] Figure 6 This is a scanning electron microscope (SEM) image of the conductive copper film obtained after sintering the copper paste in Example 4. Detailed Implementation

[0028] The present invention will be further described below with reference to specific embodiments, but these should not be construed as limiting the invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.

[0029] Example 1

[0030] 1. Ascorbic acid, polyvinylpyrrolidone (PVP), and polyethylene glycol (PEG) in a mass ratio of 4:3:1 were added to a 65% aqueous ethanol solution and mixed. The mixture was stirred in an oil bath at 65°C for 30 minutes to obtain an organic coating solution. Copper powder was added and the mixture was stirred in an oil bath at 60–75°C for 3 hours. The mixture was then pulverized in an ultrasonic homogenizer for 2 hours. After standing, the supernatant was discarded, and the mixture was dried at 65–80°C under nitrogen purging to obtain copper powder coated with PVP.

[0031] 2. 15.3 wt% silica, 41.8 wt% boric acid, 39.8 wt% calcium carbonate, 1.6 wt% sodium carbonate, 1.1 wt% potassium carbonate, and 0.3 wt% copper oxide were placed in a nylon ball mill tube and ground in a ball mill for 3 hours. After sieving and drying, a mixed powder was obtained. The mixed powder was placed in a corundum crucible and then placed in a high-temperature sintering furnace. The temperature was increased to 400℃ at a rate of 8℃ / min and held for 10 minutes. Then, the temperature was increased to 1400℃ at a rate of 10℃ / min and sintered for 60 minutes to prepare a glass melt. The glass melt was poured into cold water at 15-25℃ for water quenching. After the glass cooled, it was placed in a nylon ball mill jar and ball-milled for 36 hours. Then, it was sieved and dried to obtain glass powder.

[0032] The ball-to-material ratio during the ball milling process is 3:1. Zirconium balls of 6mm, 2mm, and 1mm in size are used with a mass ratio of 4:2:1. Anhydrous ethanol is used as the milling medium, with a solid-liquid ratio of 3:1. A sieve of 200-400 mesh is used for sieving. The drying temperature is 80-160℃.

[0033] 3. Mix 53wt% terpineol, 30wt% butyl carbitol, 3wt% ethyl cellulose, 2wt% hydrogenated castor oil, 3wt% castor oil, 5wt% ethyl acetate, 2wt% defoamer GP330, and 2wt% KH-550 aminosilane coupling agent, and stir evenly in a 60℃ oil bath with magnetic force until all solids are completely dissolved in the organic phase to obtain an organic carrier.

[0034] 4. 72 wt% copper powder coated with PVP film, 3 wt% glass powder, 23.5 wt% organic carrier, 0.8 wt% lead zirconate titanate (PZT) ceramic particles (particle size 3-15 μm), 0.2 wt% copper oxide and 0.5 wt% boron powder are pre-stirred with a magnetic stirrer for 0.5-3 hours. Then, a three-roll mill is used for grinding and leveling. The clearance between the low-speed and medium-speed rolls is 2 mm, and the clearance between the medium-speed and high-speed rolls is 1 mm. After each rolling, the clearance is adjusted to 0.2 mm. The rolling is repeated 6-10 times to obtain the conductive copper paste with internal electrodes.

[0035] 5. The conductive copper paste of the internal electrode is printed onto the PZT thick film using screen printing. After leveling at room temperature, it is dried at 60-80℃ and then sintered at 930℃ for 24 hours under a nitrogen atmosphere. The nitrogen atmosphere is maintained and the furnace is cooled to room temperature to obtain a conductive copper film.

[0036] Figure 1 This is a comparison of scanning electron microscope (SEM) images of the copper powder used in Examples 1-4 before and after treatment. In the image, (a) shows copper powder, and (b) shows PVP-coated copper powder. Figure 1 It can be seen that copper powder coated with PVP is more evenly dispersed, and the particle size of copper powder does not change significantly before and after coating. Figure 2 The XRD patterns are of the PVP-coated copper powders from Examples 1-4. Figure 2 It can be seen that the coated copper powder crystal phase is relatively pure, and no other impurity peaks are present, indicating that the copper powder did not oxidize after treatment. Figure 3 This is a scanning electron microscope (SEM) image of the conductive copper film obtained after sintering the copper paste in Example 1. Figure 3 It can be seen that the copper film obtained in Example 1 is dense, with a few pores but overall dense and uniform, indicating that the paste has good rheological properties and high printing quality. The multilayer ceramic low-temperature co-fired internal electrode copper paste prepared using the glass powder in Example 1 can be held at 930°C for 24 hours, and the copper film has excellent performance, which is in line with the application of multilayer ceramic low-temperature co-fired internal electrode copper paste in the field of passive component preparation.

[0037] Example 2

[0038] The difference from Example 1 is that in step 5, the obtained copper paste is printed on a PZT thick film, leveled at room temperature, dried at 60-80°C, and then sintered at 930°C for 2 hours in a nitrogen atmosphere. The nitrogen atmosphere is maintained while the furnace is cooled to room temperature to obtain a conductive copper film.

[0039] Figure 4 This is a scanning electron microscope (SEM) image of the conductive copper film obtained after sintering the copper paste in Example 2. From... Figure 4 It can be seen that the copper film obtained in Example 2 is more dense and uniform than that in Example 1. Even after long-term sintering, the performance of the sintered film does not change much, indicating that it has good stability and can be used with substrate materials under different sintering conditions and can cope with more complex sintering scenarios.

[0040] Example 3

[0041] 1. Ascorbic acid, PVP, and PEG in a mass ratio of 4:3:1 were added to a 65% ethanol aqueous solution and mixed. The mixture was stirred in an oil bath at 65°C for 30 minutes to obtain an organic coating solution. Copper powder was added and the mixture was stirred in an oil bath at 60–75°C for 3 hours. The mixture was then pulverized in an ultrasonic homogenizer for 2 hours. After standing, the supernatant was discarded, and the mixture was dried at 65–80°C under nitrogen to obtain copper powder coated with a PVP film.

[0042] 2. 15.3 wt% silica, 41.8 wt% boric acid, 39.8 wt% calcium carbonate, 1.6 wt% sodium carbonate, 1.1 wt% potassium carbonate, and 0.3 wt% copper oxide were placed in a nylon ball mill tube and ground in a ball mill for 3 hours. After sieving and drying, a mixed powder was obtained. The mixed powder was placed in a corundum crucible and then placed in a high-temperature sintering furnace. The temperature was increased to 400℃ at a rate of 8℃ / min and held for 10 minutes. The temperature was then increased to 1400℃ at a rate of 10℃ / min and held for 60 minutes to prepare a glass melt. The glass melt was poured into cold water at 15-25℃ for water quenching. After the glass cooled, it was placed in a nylon ball mill jar and ball milled for 36 hours. Then, it was sieved and dried to obtain glass powder.

[0043] During the ball milling process, the ball-to-material ratio is 3:1, the zirconium balls are 6mm, 2mm, and 1mm in size with a mass ratio of 4:2:1, the ball milling medium is anhydrous ethanol, the solid-liquid ratio is 3:1, the sieve used during the sieving process is 200-400 mesh, and the drying temperature is 80-160℃.

[0044] 3. Mix 53wt% terpineol, 28wt% butyl carbitol, 1wt% hydrogenated castor oil, 7wt% emulsifier OP-4, 1wt% palmitic acid, 6wt% ethyl acetate, 2wt% defoamer GP330, and 2wt% KH-560 silane coupling agent, and stir evenly in a 60℃ oil bath under magnetic force until all solids are completely dissolved in the organic phase to obtain an organic carrier.

[0045] 4. Mix 72wt% copper powder coated with PVP film, 3wt% glass powder, 23.5wt% organic carrier, 0.8wt% PZT ceramic particles (particle size 3-15um), 0.2wt% copper oxide and 0.5wt% boron powder, and magnetically pre-stir for 0.5-3 hours. Then, use a three-roll mill for grinding and leveling. The clearance between the low-speed and medium-speed rolls is 2mm, and the clearance between the medium-speed and high-speed rolls is 1mm. Adjust the clearance by 0.2mm after each rolling. Roll 6-10 times to obtain conductive copper paste with internal electrodes.

[0046] 5. The conductive copper paste of the internal electrode is printed onto the PZT thick film using screen printing. After leveling at room temperature, it is dried at 60-80℃ and then sintered at 930℃ for 2 hours in a nitrogen atmosphere. The nitrogen atmosphere is maintained and the furnace is cooled to room temperature to obtain a conductive copper film.

[0047] Figure 5 This is a scanning electron microscope (SEM) image of the conductive copper film obtained after sintering the copper paste in Example 3. From... Figure 5 It can be seen that the copper film in Example 3 has many holes and the edges show diffusion, indicating that the rheological properties of the paste are not suitable and the printing quality is poor.

[0048] Example 4

[0049] 1. Ascorbic acid, PVP, and PEG in a mass ratio of 4:3:1 were added to a 65% ethanol aqueous solution and mixed. The mixture was stirred in an oil bath at 65°C for 30 minutes to obtain an organic coating solution. Copper powder was added and the mixture was stirred in an oil bath at 60–75°C for 3 hours. The mixture was then pulverized in an ultrasonic homogenizer for 2 hours. After standing, the supernatant was discarded, and the mixture was dried at 65–80°C under nitrogen purging to obtain copper powder coated with a PVP film.

[0050] 2. 15.3 wt% silica, 41.8 wt% boric acid, 39.8 wt% calcium carbonate, 1.6 wt% sodium carbonate, 1.1 wt% potassium carbonate, and 0.3 wt% copper oxide were placed in a nylon ball mill tube and ground in a ball mill for 3 hours. After sieving and drying, a mixed powder was obtained. The mixed powder was placed in an alumina crucible and then placed in a high-temperature sintering furnace. The temperature was increased to 400℃ at a rate of 8℃ / min and held for 10 minutes. The temperature was then increased to 1400℃ at a rate of 10℃ / min and held for 60 minutes to prepare a glass melt. The glass melt was poured into cold water at 15-25℃ for water quenching. After the glass cooled, it was placed in a nylon ball mill jar and ball-milled for 36 hours. Afterward, it was sieved and dried to obtain glass powder.

[0051] During ball milling, the ball-to-material ratio is 3:1, and the zirconium balls are 6mm, 2mm, and 1mm in size with a mass ratio of 4:2:1. Anhydrous ethanol is used as the milling medium, and the solid-liquid ratio is 3:1. The sieve used during sieving is 200-400 mesh. The drying temperature is 80-160℃.

[0052] 3. Mix 53wt% terpineol, 24wt% butyl carbitol, 5wt% ethyl cellulose, 4wt% hydrogenated castor oil, 5wt% castor oil, 5wt% ethyl acetate, 2wt% defoamer GPE-3000, and 2wt% KH-550 aminosilane coupling agent, and stir evenly in a 60℃ oil bath under magnetic force until all solids are completely dissolved in the organic phase to obtain an organic carrier.

[0053] 4. Mix 72wt% copper powder coated with PVP film, 3wt% glass powder, 23.5wt% organic carrier, 0.8wt% PZT ceramic particles (particle size 3-15um), 0.2wt% copper oxide and 0.5wt% boron powder and magnetically pre-stir for 0.5-3 hours. Then, use a three-roll mill for grinding and leveling. The clearance between the low-speed and medium-speed rolls is 2mm, and the clearance between the medium-speed and high-speed rolls is 1mm. Adjust the clearance by 0.2mm after each rolling. Roll 6-10 times to obtain conductive copper paste with internal electrodes.

[0054] 5. The conductive copper paste of the internal electrode is printed onto the PZT thick film using screen printing. After leveling at room temperature, it is dried at 60-80℃ and then sintered at 930℃ for 2 hours in a nitrogen atmosphere. The nitrogen atmosphere is maintained and the furnace is cooled to room temperature to obtain a conductive copper film.

[0055] Figure 6 This is a scanning electron microscope (SEM) image of the conductive copper film obtained after sintering the copper paste in Example 4. From... Figure 6 It can be seen that after sintering, there are a few holes and the copper film is relatively dense, but the copper and other substances (glass powder and other additives) agglomerate and are not evenly dispersed.

[0056] The viscosity of the copper paste in Examples 1-4 was tested using a rotational rheometer (at a shear rate of 10 rpm). The conductive copper film was analyzed, including observing the microstructure of the copper film surface using a scanning electron microscope (SEM), testing the sheet resistance of the copper film using a four-probe tester, and testing the adhesion of the copper film using a tensile tester according to GB / T 17473.4-2008. The results are shown in Table 1.

[0057] Table 1. Performance of the internal electrode conductive copper paste and its sintered film in Examples 1-4

[0058]

[0059] Table 1 shows the performance of the internal electrode conductive copper paste and its sintered film in Examples 1-4. As can be seen from Table 1, the internal electrode conductive copper paste of Example 2 has a moderate viscosity, meeting the requirements for screen printing, and good stability, allowing for long-term storage. The sintered copper film has low sheet resistance and strong adhesion, making it suitable for use as the internal electrode in multilayer ceramics. Example 2 has the lowest sheet resistance and good adhesion, indicating that long-term heat preservation also has some adverse effects on the copper film, but the performance difference between the two is not significant. The internal electrode conductive copper paste of Example 3 has poor stability, resulting in low-quality sintered copper film. The internal electrode conductive copper paste of Example 4 has high viscosity, making it unsuitable for printing, but it has the best stability and can be stored for a long time; however, the sintered copper film quality is also low.

[0060] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing internal electrode copper paste for low-temperature co-fired ceramics, characterized in that, Includes the following steps: S1. Ascorbic acid (reducing agent), polyethylene glycol (stabilizer), and polyvinylpyrrolidone (dispersant) are added to an ethanol aqueous solution and stirred in an oil bath at 50-80°C to obtain an organic coating solution. Copper powder is then added and stirred in an oil bath. The solution is then homogenized, allowed to stand, the supernatant is discarded, and the solution is dried under a protective or reducing atmosphere to obtain copper powder coated with a polyvinylpyrrolidone film. The mass ratio of ascorbic acid, polyethylene glycol, and polyvinylpyrrolidone is (2-5):(2-4):

1. S2. Silica, boric acid, calcium carbonate, sodium carbonate, potassium carbonate, and copper oxide are mixed and then ball-milled in a solvent. After sieving and drying, a mixed powder is obtained. The mixed powder is heated to 400-500℃ and held at that temperature, then heated to 1200-1500℃ and sintered to produce a glass melt. The glass melt is poured into cold water for water quenching. After the glass cools, it is ball-milled, sieved, and dried to obtain borosilicate glass powder. The mass ratio of silica, boric acid, calcium carbonate, sodium carbonate, potassium carbonate, and copper oxide is (12-30):(26-55):(22-50):(0.5-10):(0.5-10):(0.1-5). S3. A solvent, binder, thixotropic agent, dispersant, defoamer, silane coupling agent, and additive A are mixed and magnetically stirred in an oil bath at 60-85°C to obtain an organic carrier; the mass ratio of the solvent, binder, thixotropic agent, dispersant, defoamer, silane coupling agent, and additive A is (15-85):(0.5-10):(0.1-10):(0.1-10):(0.1-10); the solvent is one or more of terpineol, butylcarbitol, butylcarbitol acetate, dodecayl alcohol ester, or triethanolamine; the binder is ethyl... The additive is selected from one or more of cellulose, dioctyl phthalate, polyvinyl alcohol, and palmitic acid; the thixotropic agent is selected from one or more of hydrogenated castor oil, acrylic resin, glyceryl trioleate, polyamide wax, and ethyl acetate; the dispersant is selected from one or more of castor oil, OP emulsifier, tributyl phosphate, and Span 85; the defoamer is defoamer GPE-3000 or defoamer GP330; the silane coupling agent is KH-550 aminosilane coupling agent; and additive A is selected from one or more of ethyl acetate, ethyl silicone oil, acetone, and methyl ethyl ketone. S4. Copper powder coated with polyvinylpyrrolidone film, borosilicate glass powder, organic carrier and additive B are magnetically stirred, and then ground and leveled using a three-roll mill. After each rolling, the gap is adjusted to 0.2~0.5mm, and the rolling is repeated to obtain conductive copper paste with internal electrodes. The mass ratio of copper powder coated with polyvinylpyrrolidone film, borosilicate glass powder, organic carrier and additive B is (60~80):(0.5~15):(15~40):(0.1~2). The additive B is one or more of lead zirconate titanate ceramic particles, alumina, copper oxide, bismuth oxide and boron powder.

2. The method for preparing internal electrode copper paste for low-temperature co-fired ceramics according to claim 1, characterized in that, The copper powder in step S1 has a purity of over 99% and an average particle size of 500~2000nm; the volume ratio of the copper powder to the organic coating liquid is 1:(8~20); and the concentration of the ethanol aqueous solution is 40~80wt%.

3. The method for preparing internal electrode copper paste for low-temperature co-fired ceramics according to claim 1, characterized in that, The mass ratio of the solvent in step S2 to the total mass of silicon dioxide, boric acid, calcium carbonate, sodium carbonate, potassium carbonate and copper oxide is 1:(0.5~2).

4. The method for preparing internal electrode copper paste for low-temperature co-fired ceramics according to claim 1, characterized in that, The solvent in step S2 is anhydrous ethanol and / or deionized water; the sieve used for sieving is 200-400 mesh; the protective atmosphere is nitrogen, argon, helium or neon, and the reducing atmosphere is a nitrogen-hydrogen mixture, wherein the hydrogen content is 0.5-3 vol‰ of the nitrogen-hydrogen mixture; the drying temperature is 80-160℃; the heating rate to 400-500℃ is 2-8℃ / min, and the heating rate to 1200-1500℃ is 5-20℃ / min.

5. The method for preparing internal electrode copper paste for low-temperature co-fired ceramics according to claim 1, characterized in that, The particle size of additive B in step S4 is 1~20μm.

6. The method for preparing internal electrode copper paste for low-temperature co-fired ceramics according to claim 1, characterized in that, The stirring time in step S1 is 0.5~6h, the homogenization time is 0.5~3h, and the drying temperature is 60~90℃; the sintering time in step S1 is 30~120min, and the cold water temperature is 15~28℃; the stirring time in step S4 is 0.5~3h, the rolling is 5~10 times, and the parameters of the three-roll mill are: the gap between the low-speed roll and the medium-speed roll is 0.5~3mm, and the gap between the medium-speed roll and the high-speed roll is 0.5~2mm.

7. A copper paste for internal electrodes in low-temperature co-fired ceramics, characterized in that, The internal electrode copper paste is prepared by the method described in any one of claims 1-6.

Citation Information

Patent Citations

  • Inner electrode copper paste for low-temperature co-fired ceramic, and preparation method and application thereof

    CN112509727A